THE IMPACT OF PUBLIC PROTESTS AND DEMONSTRATIONS ON INDONESIA'S GOVERNANCE SYSTEM: A SYSTEMATIC LITERATURE REVIEW - Muliyati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study investigates the impact of public protests and demonstrations on the governance system in Indonesia within the context of post-Reformation electoral democracy. Through a Systematic Literature Review (SLR) of 25 reputable journal articles published between 2023-2025, this research identifies patterns, mechanisms, and outcomes of collective action on political stability, policy responsiveness, institutional legitimacy, and regulatory frameworks. The synthesis results reveal multidimensional and contextual impacts. Qualitative findings underscore that protest effectiveness highly depends on political opportunity structures, digital media utilization, and civil society coalition capacity. Protests function as vital extra-institutional correction mechanisms, yet they also potentially cause polarization and short-term erosion of trust when government responses are repressive. This study concludes that protests have become an inseparable governance sub-system in Indonesia, driving adaptation and accountability pressures, albeit with complex consequences for social cohesion and democratic procedural stability. The findings offer theoretical contributions to social movement literature and practical insights for policymakers in designing constructive responses to public protests.